Interpreting the Claim to Legitimate Authority: an Analysis of Joseph Raz's Objection Against Incorporating Moral Norms into Law - Ramiro Ávila Peres (Ethic@: an International Journal for Moral Philosophy)
From a critical review of the literature, we analyze the incompatibility between the possibility of incorporating moral principles to the law and its authoritative nature, as argued by exclusive positivists, such as J. Raz. After presenting his argument in second section, we argue in the third section that it is incompatible with commonly accepted (even by Raz)  premises of the theory of legal interpretation, or else it would lead to contradiction - unless one presupposes, within the premises, a strong version of the sources thesis (which is what Raz intends to prove). In conclusion, we return to the arguments presented, concluding with a possible difficulty for the adoption of exclusive positivism by people inside a legal practice.